Modalitas Ketahanan Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Nuri Jawa Timur Cabang Socah - Adi, Mohammad (Ulumuna: Jurnal Studi Keilsman, 2024)
This study aims to: 1) find out what modalities are owned by KSPPS NURI East Java Socah Branch. 2) to find out how the modalities of KSPPS NURI East Java Socah Branch. The research method used in this research is a qualitative research method. The data sources are sumbe prime data and secunde data sources. Data collection techniques are carried out by observation, interviews and documentation. Furthermore, data analysis techniques go through several stages, namely data reduction, data presentation and data verification. The results of this study show that the modalities possessed by KSPS NURI East Java Socah Branch in maintaining its resilience are by having four modalities, namely economic capital, cultural capital, social capital and symbolic capital. The four capitals have proven to be able to maintain the resilience of the cooperative. This is in accordance with Pierre Bourdie's theory which states that in addition to mhodal economics which is generally in material form there is capital and accompanying in every domain, namely cultural capital, social capital and symbolic capital